Influence of race performance and environmental conditions on exertional heat stroke prevalence among runners participating in a warm weather road race - Grundstein, A. J.; Hosokawa, Y.; Casa, D. J.; Stearns, R. L.; Jardine, J. F. (Frontiers in Sports and Active Living, 2019)
The New Balance Falmouth Road Race held in Falmouth, Massachusetts, U.S. is a short distance race (11.26 km) that is well-known for high rates of exertional heat stroke (EHS). Previous research has documented the increased EHS rates with hotter and more humid weather conditions, yet did not explore the influence of race pacing on EHS risk. In this study, we leverage 15 years of data to investigate if runners who experienced an EHS moderate their average paces based on weather conditions and if there is a difference in average race pace between participants who experienced an EHS and other runners. Results indicate that runners who experience an EHS do not appear to reduce their average pace with increasing WBGT warning flag categories. In addition, runners who suffer an EHS run at a faster average pace than others, even when controlling for age, gender, race performance, and starting time WBGT. This suggests the important role of metabolic heat production as a risk factor of EHS. Since race pacing is a modifiable risk factor, our findings support the need for race organizers to actively encourage runners to adjust race pacing based on weather conditions.